ANALYSIS TRANSLATION STRATEGIES IN “ANTI-HERO” SONG BY TAYLOR SWIFT IN ENGLISH TO INDONESIAN LANGUAGE - Utami Rosalina; Yasri Tika Damayanti (NextGen Education Review Journal, 2023)
Translation can be described as the activity of translating the meaning of text from one language to another or SL (source language) to TL (target language).This study focuses on the investigation of translation strategy used for Taylor Swift's song "Anti-Hero" A descriptive qualitative approach is used in this study. The process of choosing, concentrating, streamlining, abstracting, and changing the information found in the study's field notes and transcripts is sometimes referred to as the data gathering procedure. In parallel with the data collection method, data analysis was done. Out of the 18 methods based on Molina and Albir (2002), researchers can conclude that eight types of strategies are obtained from 47 data found in the translation of the lyrics to Taylor Swift's song "Anti-Hero."The strategies found include; Amplification (15 data) 32%, Borrowing (5 data) 11%, Calque (1 data) 2%, Discursive creation (1 data) 2%, Establish equivalence (11 data) 23%, literal translation (10 data) 21% and reduction (4 data) 9%. It was found that the type of amplification translation strategy was the strategy that appeared the most with a percentage of 32% of all translation techniques found so that it became the most dominant type of translation used by translators in lyrics of the song 'Anti-Hero'. While the strategies of calque and discursive creation were the fewest translation strategies with a percentage of 2% in the translation of the lyrics of the song 'Anti-Hero' from all the strategies found.